Luminescent diamond with negative electricity vacancy
By plastically deforming the precursor diamond grains under high pressure/high temperature conditions, negatively charged nitrogen vacancy defects are solved, and the problems of high production cost and low availability of luminescent nanodiamonds in the prior art are solved, achieving high efficiency and economical The production of luminescent diamond materials has expanded its application range.
Patent Information
- Application Number
- CN202380046714.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-05-26
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art methods and techniques for making luminescent nanodiamonds are expensive, energy- and time-intensive, resulting in high material costs and low availability.
By placing the precursor diamond grains under high pressure/high temperature (HPHT) conditions for plastic deformation, negatively charged nitrogen vacancy (NV-) defects are generated, thereby improving the luminescent activity and intensity of the diamond material.
The reduction of the production cost of luminescent diamond materials and the improvement of their luminescent intensity are achieved, extending the potential end-use application range of such materials.
Smart Images

Figure CN119403899A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 365,433, filed on May 27, 2022, entitled “LUMINESCENT DIAMOND WITH NEGATIVELY CHARGED VACANCIES,” the disclosure of which is hereby incorporated by reference into this application. Background Art
[0003] Laser injected fluorescence is a known technique used to better understand how biological systems function at the molecular level by individually probing biological molecules for observation. In examples, laser injected fluorescence can be applied to imaging and tracking individual molecules or particles in biological cells and the like, for example, in vivo biosensors for internal organ mapping, cell imaging, and the like. One type of material used for laser injected fluorescence is luminescent nanodiamonds, which are nanometer-sized diamond particles or grains that have been developed to emit light when excited by a light source within the desired wavelength required by the end-use application. Summary of the invention
[0004] Luminescent diamonds and methods of making the same are disclosed herein and include subjecting a volume of precursor diamond grains to high pressure / high temperature (HPHT) conditions to cause the grains to undergo plastic deformation to produce nitrogen vacancy defects in the diamond grains, which increases the luminescence activity and intensity of the resulting diamond material compared to the luminescence activity and intensity of the precursor diamond grains. In some embodiments, the HPHT conditions are performed at an elevated temperature between 1475° C. and 1800° C. or between 1600° C. and 1750° C., which causes the diamond grains to undergo plastic deformation and preferentially produce negatively charged nitrogen vacancies (NVs) in the diamond grains. - ) defects, resulting in a higher display of luminescence intensity in the red wavelength spectrum.
[0005] In some embodiments, the luminescent diamond material formed by the HPHT process includes diamond particles mechanically interlocked together and combined with a pressure transmitting medium. - ) and neutrally charged nitrogen vacancies (NV 0 ) and NVN defects or both have a higher ratio, so that the luminescent diamond material exhibits a greater level of red luminescence than the precursor diamond material used to form the luminescent diamond material.
[0006] This summary is provided to introduce a series of concepts that are further described below in the detailed description. This summary is not intended to identify key or essential features of the claimed subject matter, nor is it intended to be used as an adjunct to limit the scope of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] The features and aspects of the luminescent nanodiamonds and methods of making the same as disclosed herein will be appreciated as they will be better understood by referring to the detailed description and appendix when considered in conjunction with the accompanying drawings, in which:
[0008] Figure 1-1 is a graph showing luminescence intensity and wavelength information of diamond powder sintered at different high temperatures and when excited with a laser emitting light at 473 nm according to an embodiment of the present disclosure;
[0009] Figure 1-2 is a graph showing luminescence intensity and wavelength information of diamond powder sintered at other different high temperatures and when excited with a laser emitting light at 473 nm according to an embodiment of the present disclosure;
[0010] Figure 2-1 is a graph of the effect of sintering temperature on red luminescence intensity when diamond powder is excited with a laser emitting light at 532 nm according to an embodiment of the present disclosure;
[0011] Figure 2-2 is a graph showing luminescence intensity and wavelength information of diamond powder sintered at 1475° C. and when excited with a laser emitting light at 532 nm according to an embodiment of the present disclosure;
[0012] Figure 3 is a graph showing luminescence intensity and wavelength information of diamond powder sintered at different high temperatures and when excited with a laser emitting light at 532 nm according to an embodiment of the present disclosure;
[0013] Figure 4 is a graph showing luminescence intensity and wavelength information of diamond powder sintered at different high temperatures and when excited with a laser emitting light at 473 nm according to an embodiment of the present disclosure;
[0014] Figure 5 is a graph showing luminescence intensity and wavelength information of diamond powder sintered at different high temperatures and when excited with a laser emitting light at 532 nm according to an embodiment of the present disclosure; and
[0015] Figure 6 is a block diagram illustrating the processing steps for making luminescent diamond as disclosed herein. DETAILED DESCRIPTION
[0016] In some embodiments, luminescent diamonds (e.g., photoluminescent diamonds) and methods of making the same as disclosed herein are designed in a manner that improves manufacturing efficiency and throughput, thereby increasing affordability and availability of the material for end-use applications, including, but not limited to, uses in optically detected magnetic resonance (ODMR). In addition, in some embodiments, luminescent diamonds as prepared according to the principles disclosed herein exhibit luminescence intensity levels similar to or greater than those of conventional luminescent diamonds, thereby providing an opportunity to expand the range of potential end-use applications for such materials. For example, the technology combined with ODMR can be powerful enough to increase the sensitivity of spin resonance spectroscopy by several orders of magnitude.
[0017] For the sake of clarity, in some embodiments, the luminescent diamond as disclosed herein is initially formed by consolidation and compaction of pre-existing diamond grains, forming a luminescent active sintered body or block (characterized by a high degree of intercrystalline diamond bonding) or forming a mechanically combined semi-sintered body or block (characterized by substantially no intercrystalline diamond bonding). In this case, the consolidated material may be referred to as luminescent diamond. During subsequent procedures, the size of the luminescent diamond is reduced according to the requirements of the specific end use, and in some embodiments, the size of the resulting diamond particles or grains is nanometer-scale. In some embodiments, the size-reduced luminescent diamond may be only nanometer-sized particles or may include a combination of nanometer-sized particles and coarser diamond particles. The term "nanodiamond" as used herein is understood to refer to diamond particles with an average size between 1nm and 1000nm. Although the existence of luminescent nanodiamonds may be known, the methods and techniques currently used to make such luminescent nanodiamonds are expensive, energy- and time-intensive, which not only increases the cost of the material but also limits the availability of the material. In some embodiments, any combination of cost, energy, or time may be reduced by making luminescent diamonds as disclosed herein.
[0018] In some embodiments, luminescent nanodiamonds as disclosed herein may be formed by combining a volume of precursor diamond grains that may be in the form of natural and / or synthetic diamond grains and placing the volume of diamond grains in a can or container. In some embodiments, the raw diamond grains of the precursor material may have an average grain size of any value or range between 15nm and 1000μm. For example, the average grain size may be 1nm to 1000μm, 5nm to 500μm, 5nm to 100μm, 5nm to 50μm, 5nm to 1μm, 5nm to 500nm, 5nm to 200nm, 25nm to 500nm, 5nm to 30nm, 30nm to 90nm, 75nm to 500nm, 75nm to 250nm, or any other value or range therein. In some embodiments, the precursor diamond grain or powder size may therefore extend to the submicron or nanodiamond range. In some embodiments, nano-sized powders formed by mechanical crushing or detonation processes of conventional diamond powders may be employed in a similar manner. Diamond powders may be synthetic or natural in origin; however, synthetic diamond powders may generally have a higher inherent nitrogen content, which together with adjacent vacancies renders the diamond luminescently active.
[0019] In some embodiments, it is desirable that the starting diamond material have an inherent amount of nitrogen impurities consistent with the amount found in diamonds designated as type 1b (e.g., 50 ppm nitrogen or more). Nanopowders synthesized by impact synthesis also typically have a higher inherent nitrogen content. In some embodiments, the container and its contents are subjected to a high pressure / high temperature (HPHT) consolidation process using conventional pressing equipment for making polycrystalline diamond. In some embodiments, the volume of diamond grains is placed in a can or container, and the can or container may be sealed or unsealed and placed in a HPHT press and subjected to the desired sintering pressure and temperature conditions. In some embodiments, the HPHT process temperature may be in the range of 1300° C. to 2500° C., and the process pressure may be 3.0 GPa to 10 GPa. In some embodiments, the volume of diamond grains is substantially free of any catalyst material, so that the diamond material produced by the HPHT process is not fully sintered, but in the form of a semi-sintered block or body, which includes diamond grains mechanically combined together by frictional contact, cold welding, diamond self-diffusion, etc. In some embodiments, an under-sintered (i.e., semi-sintered and not characterized by a network of diamond grains bonded together using a conventional metal solvent catalyst) diamond material is produced which has an improved relative transparency compared to a sintered polycrystalline diamond body, and the transparency may increase the intensity of luminescence emission therefrom. There may also be graphite formed in porous regions of the semi-sintered body which may reduce the luminescence intensity. In such cases, it may be desirable for the graphite material to be partially or completely removed as part of the manufacturing process.
[0020] During the HPHT process, it has been found that at least a portion of the volume of precursor diamond grains undergoes plastic deformation. In some embodiments, the extent of the HPHT consolidation process is such that sufficient plastic deformation is induced in the diamond grains to produce nitrogen vacancy (NV and / or NVN) defects and / or N3 optical centres in the diamond grains that act to render the diamond grains luminescence active. Plastic deformation of the diamond particles during HPHT is believed to produce vacancies as deformation mechanisms (such as crystal dislocation motion) become active, which in turn can combine with nitrogen impurities to form NV, NVN or N3 optical centres that produce the desired luminescence activity. In some embodiments, this occurs during conventional sintering of polycrystalline diamond with a metal catalyst (such as cobalt that acts to promote intercrystalline diamond bonding during the HPHT process) or a non-metallic catalyst / pressure transmission medium (such as carbonates and chlorides that do not promote intercrystalline diamond bonding during the HPHT process). In some embodiments, the diamond grains produced by the HPHT process may undergo severe plastic deformation, with extensive NV, NVN defects and / or N3 centers, and weak diamond-diamond bonding compared to solvent catalyst bonded polycrystalline diamond. For example, in some embodiments, the diamond grains induce such plastic deformation during the HPHT process that produces luminescence activity without producing a fully sintered body, thereby making downstream processes such as sizing the diamond grains by a crushing process easier and less energy intensive, as primarily or only mechanically bonded diamond grains need to be separated.
[0021] In some embodiments, luminescent diamond as disclosed herein may be formed by subjecting a volume of diamond precursor grains to an HPHT process in the presence of a catalyst material. In such embodiments, the type of catalyst material used may be selected from the group including, but not limited to, Co, Fe, Ni, carbonates, Si, and combinations thereof, for forming polycrystalline diamond (PCD). In some embodiments, HPHT treatment conditions for cobalt PCD may be within a temperature of 1300° C. to 1500° C. and a pressure of 5.0 GPa to 7.5 GPa. In addition, the cobalt PCD may be heat treated in a vacuum at a temperature of 600° C. to 700° C. (e.g., after PCD formation, before sizing, and / or after sizing).
[0022] The amount of catalyst material used can and will vary depending on factors such as the type of catalyst used, the amount of luminescence desired, the sintering temperature, and the specific end-use application. In biological end-use applications, the presence of metallic materials in the luminescent diamond may not be desired and / or permitted for biocompatibility reasons, in which case it may be desirable to use a non-metallic catalyst. In some embodiments, the use of a non-metallic catalyst results in a PCD body having relatively higher transparency or reduced opacity compared to PCD formed using a metal solvent catalyst. In some embodiments, non-metallic catalysts that can be used to make luminescent diamond as disclosed herein include carbonate catalysts such as sodium carbonate, magnesium carbonate, calcium carbonate, etc., resulting in the formation of carbonate PCD (CPCD).
[0023] In some embodiments, the amount of such carbonate catalyst may be an amount sufficient to form a fully sintered carbonate PCD body (e.g., up to 5 wt. % based on the total weight of the carbonate catalyst and diamond grains). Carbonate PCD appears to be inherently brighter / more transparent than cobalt PCD, which is believed to contribute to the higher luminescence emission and intensity levels. In some embodiments, HPHT treatment of carbonate PCD may be at a temperature of 1000°C to 2500°C (e.g., 1400°C to 2100°C, 1500°C to 1800°C, or 1600°C to 1750°C) and at a pressure greater than 6 GPa or greater than 7.0 GPa. In addition, carbonate PCD may be heat treated in an inert or vacuum environment to a temperature of 500°C to 1300°C (e.g., after forming, before and / or after sizing). In other examples, a fluoride or chloride catalyst may be used as a pressure medium (e.g., sodium fluoride / sodium chloride, magnesium fluoride / magnesium chloride, calcium fluoride / calcium chloride, etc.) in appropriate amounts and HPHT treatment conditions.
[0024] As with the embodiments described herein, the HPHT treatment produces plastic deformation in the diamond grains, thereby producing NV, NVN and / or N3 centers that cause increased levels of luminescence activity / intensity compared to the precursor diamond grains. Some vacancies formed during HPHT may not combine with nitrogen during the plastic deformation process and may migrate to the vicinity of nitrogen sites during the heat treatment, thereby producing additional NV, NVN and / or N3 sites. The higher processing temperature and pressure conditions involved in carbonate PCD can produce a higher degree of plastic deformation in the diamond grains, and therefore produce higher luminescence activity. The use of higher heat treatment temperatures can also promote additional NV, NVN and / or N3 centers, and therefore promote higher luminescence activity.
[0025] In some embodiments, it may be desirable to use an amount of catalyst material that is less than that used to form a fully sintered PCD body (e.g., less than 5 wt. % catalyst compared to the total weight of the diamond layer or PCD body). In such embodiments, it may be desirable to produce a partially sintered or semi-sintered PCD body that includes intercrystalline bonded diamond and free diamond grains for the purpose of simplifying the downstream process of sizing the PCD body into nano-sized diamond fragments or grains. It has been found that PCD made in the manner disclosed herein produces luminescence intensity levels that are greater than the luminescence intensity levels of conventional luminescent nanodiamonds, and for this reason, producing a product having some PCD during HPHT processing (even if a fully sintered diamond body is not produced) can provide the desired increase in luminescence intensity while also making the downstream sizing process relatively easier and less energy intensive than a process involving a fully sintered PCD body. Thus, by adjusting the amount of catalyst material, diamond material having a desired degree of sintering that produces a desired increase in luminescence intensity can also simplify the downstream sizing process.
[0026] In further cases, it has been observed that luminescence of certain wavelengths can be further improved by controlling processing conditions. For example, NV centers in diamond can produce red luminescence (e.g., with a peak centered at about 650 nm), NVN centers in diamond can produce green luminescence (e.g., with a peak centered at about 525 nm), and N3 centers in diamond can produce blue luminescence (e.g., with a peak centered at about 450 nm) and violet-blue luminescence (e.g., with a peak centered at about 415 nm). In some materials, luminescence of one or more colors and intensities can be preferentially produced by controlling the number of NV, NVN, and / or N3 centers, and for some applications, luminescence of one or more colors may be more desirable than other colors. In one example, ODMR can be used in conjunction with red luminescence, meaning that it may be desirable to produce NV centers.
[0027] With respect to NV centers, at least two types of centers can be formed. Specifically, negatively charged NV centers (NV - ) to produce red luminescence because they can have a zero photon line (ZPL) at about 635nm. In contrast, non-charged (NV 0 ) may have a ZPL at about 575 nm and thus be closer to the green spectrum. - Red illumination of the center may be particularly suitable for analysis by ODMR. As described above, the technique may be very powerful and can increase the sensitivity of spin resonance spectroscopy by several orders of magnitude. Thus, one aspect of the present disclosure relates to preferentially controlling NV when producing nanodiamond particles (e.g., using a HPHT sintering process). 0 and NV-The method and diamond material of the center.
[0028] It has been found that neutral and negative (NV 0 / NV - ) ratio may depend on various factors, including particle size and the temperature of the HPHT sintering process. For example, Figure 1-1 and Figure 1-2 1 and 100 - 2 (collectively, FIG. 100 ) are graphs of luminescence intensity versus wavelength showing the effect of HPHT temperature on diamond grains (containing no catalyst material and subjected to a cell pressure of 6.5 GPa) over a range of different temperatures from 1000° C. to 2000° C. Specifically, the graphs show the luminescence characteristics of diamond grains subjected to HPHT processes at 1000° C., 1100° C., 1200° C., 1300° C., 1375° C., 1425° C., 1475° C., 1625° C., 1700° C., 1800° C., and 2000° C.
[0029] The diamond grains subjected to each of the above HPHT processes had an average grain size of 100 nm. As shown in the figure, the materials each had a certain luminescence level at a wavelength of 500 nm to 900 nm, with a peak of green luminescence at about 520 nm to 570 nm (corresponding to NV 0 and NVN centers), and the peak of red emission is about 620nm to 720nm (corresponding to NV - In this test, it is apparent that, depending on the HPHT temperature, both red and green luminescence can be produced in the same diamond material. It will therefore be appreciated that luminescent diamonds as disclosed herein can be made to display luminescence of one or more different wavelengths, which can be optimized to suit a particular end-use application. Furthermore, there is not always a direct correlation between red and green luminescence. For example, depending on the HPHT temperature, Figure 1-2 , the powders sintered at 1625℃ and 1700℃ have relatively lower intensity green luminescence, but relatively higher intensity red luminescence, compared with the powders sintered at 1800℃ and 2000℃. Figure 1-1 The lines in the same Figure 1-2 The other powders in the sample had significantly lower green luminescence, but were accompanied by some red luminescence, indicating that NV was preferentially produced. - , but lower than the powders sintered at 1625℃ and 1700℃.
[0030] Figure 1-1 and Figure 1-2The luminescence characteristics shown in (collectively referred to as FIG1 ) were produced by subjecting the HPHT treated diamond samples to 473 nm blue laser irradiation, as collected with a micro-spectrometer. These tests represent the results of tests conducted on pellet or powder material formed after HPHT sintering. In these tests, it has been shown that HPHT temperature conditions of 1000°C to 2000°C preferentially produce NV - The HPHT temperature condition of 1800°C to 2000°C shows relatively low luminescence due to NVN centers, because temperatures above 1800°C appear to convert NV centers to NVN centers and weaken the red intensity, which is shown as a decreased red wavelength. At lower temperatures of 1000°C to 1475°C, the red luminescence peak is still obvious, but at a lower intensity, which may correspond to a higher number of NV 0 In this example, temperatures between 1600°C and 1750°C appear to be taking precedence over NV 0 Centers and NVN centers generate NV - The central aspect is particularly effective, which increases the red luminous intensity.
[0031] Figure 2-1 and Figure 2-2 (collectively referred to as FIG. 2 ) are graphs 200 - 1 , 200 - 2 (collectively referred to as 200 ) which further illustrate the effect of sintering temperature on the generation of NV centers (and in particular NV - The impact of the priority of the center). Figure 2-1 The luminescence intensity of diamond powder when excited by a 532 nm green laser when sintered at temperatures between 1475° C. and 2000° C. is shown. The diamond material is formed from diamond grains having an average particle size of 100 nm. Figure 2-2 is a graph of the intensity of a material sintered at 1475°C and within wavelengths between 550nm and 850nm. Figure 2-1 and Figure 2-2 The test results in the graph in Figure 2 show that although the red luminescence intensity increases for the material sintered at 1475°C (reflecting the NV 0 and NV - The red luminescence intensity of diamond materials sintered in the temperature range between 1600°C and 1750°C is even higher, showing even more NV - In contrast, the red intensity at 1800℃ and 2000℃ decreases significantly, which may be due to the increased generation of NVN centers.
[0032] Figures 3 to 51 and 2. Further graphs 300, 400, 500 are examples of the effect of temperature on red luminous intensity, but using a different granularity than that used for the tests reflected in the graphs 100, 200 of FIGS. 1 and 2. For example, Figure 3 and Figure 4 The graphs 300, 400 are generated by analyzing diamond powder having an average grain size of 50 nm and directly sintered by the HPHT method at a temperature between 1200°C and 2000°C. Figure 3 In Figure 1, the luminescence intensity of various materials over the visible spectrum (380nm to 750nm) and over parts of the ultraviolet (300nm to 380nm) and near infrared (750nm to 875nm) spectrum is shown. All intensities are measured when the materials are excited with a 532nm green laser.
[0033] The 50 nm particle size showed similar results to the 100 nm particle size, with particularly significant intensity in the red wavelengths when the sintering temperature was between 1650°C and 1750°C. However, significant increases in red intensity were also seen at temperatures as low as 1480°C and as high as 1800°C. Figure 2-2 When comparing the tests of the NV - However, further increases in temperature to 1900°C and 2000°C show a significant decrease in red intensity, similar to the previous examples. Lower temperatures of 1200°C to 1350°C also show some peaks in red luminescence intensity that are higher than those at temperatures above 1900°C, reflecting some NV - centers, but these peaks are significantly lower than those sintered at 1480°C to 1800°C, indicating that a higher number of NVs are still generated. 0 Specifically, for materials sintered at temperatures below 1400°C, from NV 0 The intensity at the center (ZPL at about 575 nm) is very close to that from NV - However, after increasing the sintering temperature, more NV - Center formed, and from NV - The photoluminescence of the center dominates the luminescence spectrum.
[0034] When the material was excited with a 473 nm blue laser, spectral differences were also detected for the samples, including those sintered from 1350°C to 1650°C, such as Figure 4 As shown in the curve graph 400.
[0035] Figure 5is another graph 500 showing the intensity of the red color of nanodiamond material after HPHT sintering at various temperatures. Figure 5 The graph 500 in FIG. 5 reflects tests conducted on different materials in which the average grain size was 25 nm and the materials were excited with a 532 nm green laser. As shown, sintering at temperatures between 1600° C. and 1750° C. produces a sintering temperature corresponding to NV. - The center produces a higher red luminescence, with temperatures of 1600°C to 1700°C being particularly effective over the entire red spectrum.
[0036] Figure 6 6 is a block diagram 600 illustrating a process that may be used to make a luminescent diamond. In some embodiments, the process may be implemented in a series including two or more of the steps shown. In a first process 602, materials that may be used to make a luminescent diamond are combined and assembled in a manner discussed herein, which may or may not include the use of a catalyst material, and includes subjecting the assembled or combined materials to a HPHT process, which may or may not result in the formation of a fully sintered diamond compact. In some embodiments, the first process 602 generates vacancies / centers in the resulting diamond material to form nitrogen (NV 0 NV - , NVN and / or N3), as discussed herein. In a second optional process 604, the diamond material produced by the first process 602 is subjected to a heat treatment process. The heat treatment is optionally performed under vacuum conditions. An example heat treatment may include an annealing process optionally performed at a temperature above 500°C.
[0037] Referring to the luminescence intensity results, in some embodiments, pressing the diamond material in the first step 602 and / or performing a heat treatment in step 604 may increase the luminescence intensity of the diamond material (e.g., by increasing the NV count for red intensity, including the ratio of NV centers to NVN centers and / or NV - Center and NV 0 In a third optional process 606, the diamond material from process one 602 or process two 604 is collected or reduced in size by crushing, grinding, grinding, or other sizing techniques. The size of the diamond particles formed during this third step 606 may depend on the specific end-use application of the luminescent diamond material as the particles are crushed, ground, milled, etc. During this third process 606, the diamond material may be converted to a powder. In some embodiments, reducing the size of the diamond material increases the luminescence intensity of the diamond material (e.g., by a factor of 3 to 4 due to the increased surface area of the resulting powder).
[0038] Optionally, the third process 606 may collect or generate powder without crushing, grinding, milling, etc. For example, the HPHT process in step 602 may be performed with a pressure transmitting medium that does not promote diamond-to-diamond intercrystalline bonding and does not act as a catalyst for diamond synthesis. For example, sodium chloride (NaCl) may be used to transmit pressure between diamond grains and deform them as discussed herein to produce NV, NVN or N3 vacancies. In some cases, the resulting material may remain in a grain or powder form that may be collected without milling, grinding, etc. For example, a raw precursor diamond powder having an average size of 1 nm to 90 nm (e.g., 1 nm to 30 nm, 30 nm to 90 nm, etc.) may be subjected to an HPHT process with a pressure transmitting medium and produce a treated diamond powder having a similar average size. In some cases, the size may be slightly reduced, or the relative proportions may be changed (e.g., spherical diamond grains become elliptical diamond grains).
[0039] In a fourth optional process 608, the diamond material from process one 602, process two 604, or process three 606 is subjected to an air heat treatment (e.g., an oxidative heat treatment). In some embodiments, the air heat treatment causes the surface of the diamond material to whiten, which is believed to be due to the formation of oxygen terminated diamond bonds. In some embodiments, subjecting the diamond material to this fourth process 608 increases the luminescence intensity by up to about 10 times. In some embodiments, luminescent diamond material as disclosed herein may be formed according to one or more of these processes, and in some embodiments, all of these processes are used in an ordered sequence depending on the type and / or degree of luminescence intensity required for a particular end-use application.
[0040] In some embodiments where the luminescent diamond obtained from the HPHT process is in the form of metallic PCD (e.g., cobalt PCD), it may be desirable to treat the sintered PCD body to fully or partially remove metallic material therefrom, which may be done by a leaching process or other process known in the art to remove metal catalysts from PCD, to enable use in applications where the presence of those metals is undesirable or impermissible or impractical (e.g., biological applications). Additionally, removal of catalyst material from the PCD may weaken the structure of the sintered body, making it more susceptible to crushing and size reduction.
[0041] In some embodiments of luminescent diamond (e.g., carbonate PCD) formed using a carbonate catalyst as disclosed herein, such metal-free PCD is metal-free and can therefore be used in biological or other end-use applications without requiring any catalyst removal. In some embodiments, it may be helpful to use magnetic separation techniques to ensure that the luminescent diamond material is substantially free of metal catalyst. In some embodiments of luminescent diamond provided in the form of carbonate PCD, luminescence intensity levels significantly higher than cobalt PCD are obtained, which may be due to the higher temperature and pressure levels used in the HPHT sintering process employed for carbonate PCD, as well as the relative increase in transparency and decrease in opacity of carbonate PCD compared to cobalt PCD, as described above.
[0042] Luminescent diamonds as disclosed herein may be sized after the HPHT consolidation process to facilitate use in applications requiring smaller sized diamond particles (e.g., nano-sized particles), such as in biological applications as discussed above. Thus, after the luminescent diamond has been consolidated by HPHT treatment, it is subjected to a size reduction treatment for the purpose of dividing the diamond material into smaller sized diamond fragments or grains. In some embodiments, the luminescent diamond may be treated to reduce the size to an average diameter of 1 nm to 1 mm or 5 nm to 200 μm, etc. Examples of useful average particle size ranges include, but are not limited to, 5 nm to 100 nm, 100 nm to 200 nm, 200 nm to 1000 nm, 500 nm to 20 μm, or 20 μm to 200 μm. In some embodiments, an average particle size of 1 μm or greater may be useful. The specific process used to reduce the size of the diamond material resulting from the HPHT treatment can and will vary depending on the specific material (e.g. whether the diamond material is in the form of sintered PCD, partially sintered PCD or mechanically assembled diamond grains) and / or the final size desired after treatment.
[0043] In some embodiments, the diamond material may be broken by high-speed impact with a high-strength target (e.g., a target made of tungsten carbide, etc.) or by impact with another diamond material (e.g., self-impact under high-speed conditions). In some embodiments, such as where the diamond material is to be used in biological applications, it may be desirable to reduce the diamond material to nano-sized fragments or particles. If the high temperature or ambient temperature conditions help to make the process of reducing or sizing the diamond material easier, or if the high temperature or ambient temperature conditions cause the diamond material to undergo further plastic deformation to further increase the luminescent activity and luminescent intensity, the process may be implemented under high temperature or ambient temperature conditions. Sorting by magnetic or other mechanical techniques can be used for the purpose of separating luminescent diamond particles with cobalt inclusions from luminescent particles without cobalt inclusions. In some end-use applications, the shape of the resulting particles may be relevant because some honeycomb structures are sensitive to sharp edges such as those produced by fragmented diamond crystals. In these applications, it may be desirable to use detonation nanodiamonds as the starting material because these particles are essentially spherical in shape. In some embodiments, it has been shown that treating the material in an oxidizing environment as described removes 50% or more of the diamond crystals under some conditions, which can be employed to remove sharp edges and increase the sphericity of the particles. In the above powder sizing, adequate definition of particle size can be achieved by employing the equivalent circle method of equal projected area, as given by Defined by, where D EQPC is the diameter of a circle having the same projected area A as the particle of interest.
[0044] As described herein, during the process of reducing the diamond material to a desired diamond particle size (e.g., nano-sized particles), the diamond material may undergo further plastic deformation or fracture (e.g., beyond the plastic deformation or fracture that occurred during the HPHT process), resulting in a further increase in the luminescence activity and luminescence intensity of the resulting diamond material. As a result, the resulting sized diamond particles may have a luminescence intensity level that is greater than the luminescence intensity level of the diamond material after the HPHT process. Furthermore, if intermediate treatments such as those discussed herein are performed between the HPHT process and sizing, there may be a double increase in luminescence activity / intensity between the diamond material in a consolidated state during after the HPHT process and the diamond particles after the reduction or sizing process.
[0045] It should be understood that the amount of increase in luminescence intensity may vary depending on factors such as the particular type of luminescent diamond material, the size of the grains in the precursor diamond material, the technique or process used to reduce the processed diamond material, the final size of the luminescent diamond particles, and other process treatments employed (such as heat treatment under vacuum conditions and / or air heat treatment). In addition to exhibiting a luminescence intensity greater than that of conventional or other luminescent nanodiamonds, the luminescent diamonds as described herein maintain their luminescence intensity for a longer duration than conventional luminescent nanodiamonds.
[0046] As discussed herein, the precursor diamond material may have a variety of sizes, which may affect at least the luminescence intensity. In some cases, the size of the precursor material combined with the temperature of the HPHT process may affect the luminescence intensity. Examples of useful average grain sizes vary for the precursor diamond material, but are not limited to materials between 1 nm and 1 mm, and any range with lower and upper endpoints therebetween. In some specific examples, the average size of the grains in the precursor material may be 1 nm to 100 nm, 1 nm to 30 nm, 30 nm to 90 nm, 100 nm to 200 nm, 100 nm to 45 μm, 200 nm to 1000 nm, 500 nm to 20 μm, or 20 μm to 200 μm. In some embodiments, an average grain size of 1 μm or more may be useful, while in other embodiments, an average grain size of less than 100 nm (e.g., less than 90 nm) may be useful.
[0047] Various temperatures may also be used during the HPHT process. In some embodiments, the maximum sustained temperature is between 1000°C and 2500°C, but any range having lower and upper endpoints therebetween may also be used. For example, a suitable range may include lower and upper limits including any of the following: 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1425°C, 1450°C, 1475°C, 1500°C, 1525°C, 1550°C, 1575°C, 1600°C, 1625°C, 1650°C, 1675°C, 1700°C, 1725°C, 1750°C. ℃, 1775℃, 1800℃, 1825℃, 1850℃, 1875℃, 1900℃, 1925℃, 1950℃, 1975℃, 2000℃, 2025℃, 2050℃, 2075℃, 2100℃, 2150℃, 2200℃, 2250℃, 2300℃, 2350℃, 2400℃, 2450℃, 2500℃, or any value therebetween. Thus, by way of illustration, in some embodiments, the temperature of the HPHT process can be in the range of 1000℃ to 2500℃, 1450℃ to 1900℃, 1475℃ to 1850℃, 1575℃ to 1775℃, 1600℃ to 1800℃, 1600℃ to 1750℃, or in other ranges derived from the above endpoints.
[0048] As described herein, luminescent diamonds may be formed using non-catalyst materials that do not promote intercrystalline diamond bonding during the HPHT process to produce a body that is free of (e.g., substantially free of) intercrystalline diamond bonding. Such materials may be considered to be pressure-transmitting media. As used herein, pressure-transmitting media refers to materials that act during the HPHT process to promote mechanical bonding of diamond to diamond. Thus, in contrast to materials that promote high intercrystalline diamond to diamond bonding. Thus, pressure-transmitting media may promote weak intercrystalline diamond to diamond bonding or no intercrystalline diamond to diamond bonding, but rather favor mechanical bonding. Examples of pressure-transmitting media materials that may be used to make luminescent diamonds include, but are not limited to, carbonates, nitrates, sulfates, phosphates, chlorates, perchlorates, acetates, chromates, oxalates, sulfides, ammonium compounds, hydroxides, oxides, cyanides, cyanates, dichromates, halides, chlorides, fluorides, or combinations thereof. The pressure transmitting medium may be selected from materials that promote diamond growth but do not promote high intercrystalline diamond-to-diamond bonding, such as sodium carbonate (Na2CO3) and other alkali metal carbonate materials or compounds, or other functionally similar materials.
[0049] The pressure transmitting medium may be selected from materials that are not catalysts for diamond synthesis, such as sodium chloride (NaCl) or sodium fluoride (NaF) and other chloride or fluoride materials or compounds, or other functionally similar materials. In some embodiments, it is desirable that the material selected as the pressure transmitting medium is water soluble, acid soluble, or alkali soluble to facilitate removal from the luminescent diamond formed by HPHT treatment by water washing, acid washing, or alkali washing. The pressure transmitting medium may be liquid or solid at room temperature and at one atmosphere of pressure. In some embodiments, the pressure transmitting medium may be provided in solid form for ease of handling during HPHT container loading. Furthermore, while different types of pressure transmitting media have been described, it should be understood that the pressure transmitting medium used may be single-phase, such as NaCl or Na2CO3, or the pressure transmitting medium may contain two or more phases of different materials, such as NaCl-Na2CO3 or a NaCl-KCl-LiCl mixture, etc. The use of a two or more phase pressure transmission medium mixed composition enables the desired melting point of the pressure transmission medium to be widely varied and controlled during the HPHT process, for example, to ensure that the pressure transmission medium is in a liquid state during HPHT treatment to fill the interstices (e.g., most or all of the interstices) between the diamond particles, thereby minimizing or eliminating diamond surface graphitization.
[0050] In some embodiments, luminescent diamonds may be made in a manner similar to that disclosed above, wherein a volume of nano- or micron-sized diamond grains or powder is premixed with a pressure transmitting medium such as Na2CO3, NaCl and / or NaF powder. When subjected to the HPHT process, the pressure transmitting medium acts to transmit pressure to the diamond particles and also fills the voids between the diamond particles to minimize or eliminate diamond graphitization. During the HPHT process, a shear load is applied to the diamond particles through point contacts of diamond to diamond particles, which acts to induce plastic deformation at high temperatures, which produces NV, NVN and / or N3 defects / centers. In some embodiments, the volume percentage of precursor diamond grains is controlled to ensure the generation of such point contacts and the resulting shear loads. In some embodiments, the amount of precursor diamond grains used is greater than 20 volume %, and in some embodiments, greater than 50 volume %, based on the total volume of the diamond grain and pressure transmitting medium mixture. In some embodiments, the amount of pressure transmitting medium may also be controlled to ensure that it fills the open spaces between the diamond grains to minimize or prevent graphitization of the diamond surface at high temperatures. In some embodiments, the amount of pressure transmitting medium used is greater than 5 volume %, and in some embodiments, greater than 10 volume %, based on the total volume of the diamond grain and pressure transmitting medium mixture.
[0051] Although the methods of making luminescent diamond disclosed above involve premixing of diamond grains and a pressure transmitting medium, it should be understood that the diamond grains may be loaded into a HPHT container (e.g., a refractory metal box) without being premixed with a pressure transmitting medium. In such examples, the pressure transmitting medium may be provided in the form of one or more layers or bodies placed adjacent to one or more layers of diamond grains inside the container. At the high temperatures during the HPHT process, the pressure transmitting medium may melt and penetrate into the volume of the diamond grains by the applied pressure. In some embodiments, the layer or body of pressure transmitting medium has a sufficient volume to ensure complete penetration of the volume of the diamond grains.
[0052] For use of luminescent diamonds as disclosed herein in certain downstream applications such as biological uses, it may be desirable to further treat or functionalize the luminescent diamond particles (e.g., nanodiamonds) to adapt the material for its intended use. The treatment regime and type that may be used to functionalize the luminescent diamond material as disclosed herein should be understood to vary depending on the specific end-use application. However, an exemplary functionalization process may be a process involving achieving oxygen termination along the diamond surface to render the diamond surface hydrophilic, and may be established through a series of surface oxidation processes. Such oxygen-terminated functionalization may include providing a mixture of =O, -OH, -COOH, or -COC- groups on the surface. Other surface terminations may include hydrogen termination, halogenation, thermal annealing to produce double bonds, and reduction to OH termination. Another type of functionalization may involve grafting or attaching certain molecules to a treated diamond surface as treated in a manner indicated to promote such attachment, wherein such molecules are selected to readily react with different biomolecules. Yet another type of functionalization may include biomarkers, which may occur through electrostatic (non-covalent) or covalent binding attachment between diamond particles and biomolecules. These are just a few of the ways in which luminescent diamonds as disclosed herein may be functionalized for use in biological applications, and it will be appreciated that other known methods and techniques that may be used to functionalize luminescent diamonds for specific biological uses are within the scope and spirit of the present disclosure.
[0053] Although only a few example embodiments of luminescent diamonds are described in detail above, it will be readily apparent to those skilled in the art that many modifications may be made in the example embodiments without substantially departing from the present invention. For example, luminescent diamonds as disclosed herein have been presented in the context of biological end-use applications and / or in combination with optically detected magnetic resonance processes. It should be understood that luminescent diamonds as disclosed herein may be used in end-use applications other than biological or in combination with detection methods other than optically detected magnetic resonance, where the desired improved level of luminescence intensity is useful or beneficial. Other potential uses of luminescent diamonds include, but are not limited to, use in magnetic sensors, high-resolution thermal imaging, microscopic sensor arrays, anti-counterfeiting measures, ion concentration monitoring, membrane potential measurement, optical trapping, quantum computing, and strain / pressure sensors. Therefore, it should be understood that luminescent diamonds as disclosed herein are not intended to be limited to one particular end-use application or detection mechanism. It should be understood that reference to "one embodiment," "embodiment," "example," etc. of the present disclosure is not intended to be interpreted as excluding the existence of additional embodiments that also incorporate the features. For example, although features of the materials and processes herein are shown or described, they may also be combined. In fact, any element or feature described with respect to an embodiment herein may be capable of being combined with any element or feature of any other embodiment described herein.
[0054] Certain descriptions or designations of components as "first," "second," "third," and the like are used to distinguish between identical components or components that are similar in purpose, structure, or operation. Such language is not intended to limit a component to a single designation or to require multiple components. Thus, a component referenced as a "first" component in a claim may be the same as or different from a component referenced as "component" or even the "first" component in the specification, and a claim may include a "first" component without requiring the presence of a "second" component.
[0055] In addition, although the specification or claims may refer to "additional" or "other" elements, features, aspects, components, etc., this does not exclude the presence of a single element or more than one additional element. When the claim or specification refers to "a / an" element, such reference should not be interpreted as only one of the elements, but should include other components and should be understood as "at least one" of the elements. It should be understood that when the specification states that "may", "may", "can" or "can" include a certain component, feature, structure, function or characteristic, the specific component, feature, structure or characteristic is provided in certain embodiments, but is optional for other embodiments of the present disclosure. The terms "connection", "connected", "connection", "connected", "connected", "connected with..." and "connected" refer to "directly connected with..." or "connected with..." via one or more intermediate elements or members. "Integrally" or "integrally" formed components include components made of the same piece of material or a group of materials, such as by being co-molded or cast by the same material, co-molded or cast in the same molding or casting process, or co-processed by the same piece of material stock. Components that are “integral” should also be understood to be “coupled” together.
[0056] As will be appreciated by those of ordinary skill in the art encompassed by the embodiments of the present disclosure, any number, percentage, ratio, or other value stated herein is intended to include that value, as well as other values that are "about" or "approximately" the stated value. Thus, stated values should be interpreted broadly enough to encompass values that are at least close enough to the stated value to perform the desired function or achieve the desired result. Stated values include at least the variations expected in suitable manufacturing or production processes, and may include values within 5%, within 1%, within 0.1%, or within 0.01% of the stated value.
[0057] The terms "approximately," "about," and "substantially," if used herein or in the claims, refer to an amount that is within standard manufacturing or process tolerances or that is close to the stated amount and still performs the desired function or achieves the desired result. For example, the terms "approximately," "about," and "substantially" may refer to an amount within a range of less than 5%, less than 1%, less than 0.1%, and less than 0.01% of the stated amount.
[0058] Although various example embodiments have been described in detail herein, it will be readily understood by those skilled in the art in view of the present disclosure that many modifications may be made in the example embodiments without substantially departing from the present disclosure. Therefore, any such modifications are intended to be included within the scope of the present disclosure. For example, although the present disclosure specifically relates to the formation of nitrogen vacancies and centers (e.g., NV, NVN, N3), the embodiments of the present disclosure may be extended to the formation and optimization of materials with other luminescent centers. For example, materials with silicon (Si) vacancies may be similarly formed and processed. In addition, although the disclosure herein contains many details, these details should not be construed as limiting the scope of the present disclosure or any of the appended claims, but only provide information related to one or more specific embodiments that may fall within the scope of the present disclosure and the appended claims. The features of any description in the various disclosed embodiments may be used in combination.
[0059] In view of the present disclosure, those of ordinary skill in the art will recognize that equivalent constructions do not depart from the spirit and scope of the present disclosure, and that various changes, substitutions, and modifications may be made to the embodiments disclosed herein without departing from the spirit and scope of the present disclosure. Equivalent constructions, including functional "means plus function" clauses, are intended to cover structures described herein as performing the described functions, including both structural equivalents that operate in the same manner and equivalent structures that provide the same functions. It is the express intention of the applicant not to invoke means plus function or other functional requirements for any claim, except for those claims in which the words 'means for' appear together with the associated functions. Every addition, deletion, and modification to the embodiments that falls within the meaning and scope of the claims is included in the claims.
[0060] The Abstract at the end of this disclosure is provided to allow the reader to quickly ascertain the general nature of some embodiments of the disclosure. It is understood that it will not be used to interpret or limit the scope or meaning of the claims.
[0061] The appendix included herewith is fully incorporated into this disclosure as a whole for all purposes.
Claims
1. A method for producing a luminescent diamond, comprising: A volume of precursor diamond grains is subjected to high pressure / high temperature (HPHT) conditions at an elevated temperature between 1600° C. and 1800° C. and thereby the diamond grains undergo plastic deformation to preferentially generate negatively charged nitrogen vacancies (NVs) in the diamond grains. - )defect, The resulting diamond material exhibits a luminescence intensity level in the red wavelength spectrum that is greater than the luminescence intensity level of the precursor diamond grains.
2. A method according to claim 1, wherein the luminescence intensity level in the red wavelength spectrum is greater than the luminescence intensity level of the precursor diamond grains when subjected to an elevated temperature of between 1000°C and 1450°C or between 1900°C and 2000°C.
3. The method of claim 1, wherein the resulting diamond material has a higher NV than the precursor diamond grains subjected to the high temperature between 1000° C. and 1450° C. - Neutral nitrogen vacancies (NV 0 ) defects, and has a higher ratio of NV defects to NVN defects than the precursor diamond grains subjected to the high temperature between 1900°C and 2000°C.
4. A method according to claim 1, wherein the resulting diamond material is substantially free of intercrystalline bonded diamond.
5. The method of claim 1, wherein the volume of precursor diamond grains is subjected to the HPHT conditions in the presence of a pressure transmitting medium.
6. The method of claim 5, wherein the pressure transmitting medium does not promote intercrystalline diamond bonding during the HPHT conditions.
7. The method of claim 5, wherein the pressure transmitting medium is selected from the group consisting of carbonates, nitrates, sulfates, phosphates, chlorates, perchlorates, acetates, chromates, oxalates, sulfides, ammonium compounds, hydroxides, oxides, cyanides, cyanates, dichromates, halides, chlorides, fluorides, and combinations thereof.
8. The method of claim 5, wherein the pressure transmitting medium is mixed with the volume of diamond grains prior to the HPHT condition.
9. The method of claim 5, wherein the pressure transmitting medium is placed adjacent the volume of diamond grains prior to the HPHT condition, and wherein the pressure transmitting medium melts and fills interstitial pores within the volume of diamond grains during the HPHT condition at the high temperature.
10. A method according to claim 5, wherein after the HPHT conditions, the resulting diamond material comprises greater than 20 volume % diamond and greater than 5 volume % pressure transmission medium based on the total volume of the resulting diamond material.
11. A method according to claim 5, wherein after the HPHT conditions, the resulting diamond material comprises greater than 50 volume % diamond and greater than 10 volume % pressure transmission medium based on the total volume of the resulting diamond material.
12. The method of claim 5, wherein the pressure transmitting medium is selected from the group consisting of: a water soluble material, an acid soluble material, and an alkali soluble material.
13. The method of claim 1, wherein after the HPHT conditions, the resulting diamond material comprises diamond particles in powder form, or diamond particles that are mechanically interlocked together and separable without a grinding, lapping or crushing process.
14. The method of claim 1, further comprising: After subjecting the volume of precursor diamond grains to the HPHT conditions, the resulting diamond material is washed and thereby all or a portion of the pressure transmission medium is removed therefrom.
15. The method of claim 1, wherein the elevated temperature is between 1600°C and 1750°C and the average size of the precursor diamond grains is between 50 nm and 5 μm.
16. A luminescent diamond material comprising: Diamond particles mechanically interlocked together and combined with a pressure transmitting medium, wherein the luminescent diamond material comprises diamond grains that have undergone plastic deformation by a high pressure / high temperature (HPHT) process and ... - ) and neutrally charged nitrogen vacancies (NV 0 ) and NVN defects or both have a higher ratio, so the luminescent diamond material displays a greater level of red luminescence than the precursor diamond material used to form the luminescent diamond material.
17. The luminescent diamond material of claim 16, wherein the HPHT process comprises temperature conditions between 1600°C and 1750°C.
18. Luminescent diamond material according to claim 17, wherein the diamond particles have an average particle size between 100 nm and 45 μm.
19. The luminescent diamond material of claim 16, wherein the HPHT process comprises temperature conditions between 1475°C and 1800°C.
20. The luminescent diamond material of claim 19, wherein the diamond particles have an average particle size of between 30 nm and 90 nm.
21. The luminescent diamond material of claim 19, wherein the diamond particles have an average particle size between 1 nm and 30 nm.
22. The luminescent diamond material of claim 16, the pressure transmitting medium being a material that does not promote intergranular bonding of precursor diamond grains during the HPHT process.
23. The luminescent diamond material of claim 16, wherein the pressure transmitting medium is selected from the group consisting of carbonates, nitrates, sulfates, phosphates, chlorates, perchlorates, acetates, chromates, oxalates, sulfides, ammonium compounds, hydroxides, oxides, cyanides, cyanates, dichromates, halides, chlorides, fluorides, water soluble materials, acid soluble materials, alkali soluble materials, and combinations or mixtures thereof.
24. The luminescent diamond material of claim 16, wherein the diamond particles are substantially free of intercrystalline bonded diamond.
25. The luminescent diamond material of claim 16, comprising greater than 50 volume % diamond and greater than 10 volume % pressure transmission medium, based on the total volume of the luminescent diamond material.
26. The luminescent diamond material of claim 16, further comprising a total graphite content of less than 5 wt% after being produced by the HPHT process without further processing.
27. A method as claimed in any one of claims 1 to 15, used to produce a luminescent diamond material as claimed in any one of claims 16 to 26.
28. Any method, system, assembly, apparatus, material, component, subcomponent or portion thereof as herein described or illustrated.